1985
DOI: 10.1002/cjoc.19850030404
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and adsorption: I. The structure of adsorbed layer of nonionic surfactants at SiO2/water and SiO2/cyclohexane interface

Abstract: Based on the adsorption of Triton X‐100 on silica/water and silica/cyclohexane interfaces and the adsorption of Triton X‐305 on silica/water interface, two adsorption models have been proposed. On silica/cyclohexane interface, the adsorption of Triton X‐100 is monomolecular layer. The molecules in the monolayer are presumed to be attached to the silica surface by their EO chain such that their hydrocarbon chain are exposed to the cyclohexane phase. On silica/water interface, the adsorption of Triton X‐100 or T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…12313 Thereafter, based on the mass-action model of surfactant adsorption, a theoretical approach was developed which also allows the calculation of the hemimicelle aggregation number (n), equilibrium constant ( K ) and the standard free energy of hemimicellization (AGE,) from the experimental data. l 8 The results show that the n values obtained by the mass-action model are in good agreement with those obtained by the empirical approach proposed earlier. Very recently, based on the mass-action model of one-step formation of hemimicelles, an isotherm equation was derived which explains the S-type adsorption isotherm and allows us to calculate n, K and AGim, and fits the experimental adsorption isotherms of non-ionic surfactants on silica gel very well.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…12313 Thereafter, based on the mass-action model of surfactant adsorption, a theoretical approach was developed which also allows the calculation of the hemimicelle aggregation number (n), equilibrium constant ( K ) and the standard free energy of hemimicellization (AGE,) from the experimental data. l 8 The results show that the n values obtained by the mass-action model are in good agreement with those obtained by the empirical approach proposed earlier. Very recently, based on the mass-action model of one-step formation of hemimicelles, an isotherm equation was derived which explains the S-type adsorption isotherm and allows us to calculate n, K and AGim, and fits the experimental adsorption isotherms of non-ionic surfactants on silica gel very well.…”
supporting
confidence: 84%
“…We have been engaged for years in trying to elucidate the phenomena of surfactant adsorption at solid/liquid interfaces. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Adsorption isotherms of various types, including Langmuir-type (L), S-type (S) and two plateaux-type (LS) have been reported. 6-8~10-17319920…”
mentioning
confidence: 99%
“…Gu et al and others [120][121][122][123][124][125][126][127] studied the adsorption of various types of surfactants on silica gel and generalized the followings. The adsorption isotherm of cationic surfactants on silica exhibits two plateaus.…”
Section: Adsorption Of Surfactants On Silica Surfacementioning
confidence: 99%
“…The present study was undertaken in an attempt to fill this gap. To our knowledge the only reported studies have essentially shown that the adsorption of poly(oxyethylene) glycol alkylphenyl ether onto solid surfaces has a strong solvent polarity dependence (38)(39)(40)(41)(42)(43). Adsorption depends not only on the solvent polarity but also on the difference in polarity between the solvent and the adsorbent.…”
Section: Introductionmentioning
confidence: 98%